ENSINO E SAÚDE: O QUE PENSAM E O QUE SABEM OS DEFICIENTES AUDITIVOS - Joaquim Tomé de Sousa; Sheila Araújo Teles; Andiara Pereira Martins Fonseca; Maria Cristina Magalhães; Venery Rodrigues Galvão; Helga Benneth Pires; Maria Alves Barbosa (Universidade Federal de Goias, 1999)
Field work accomplished in the Special School Elysio Campos of Goiânia year of 1997 through PROGRAD / Program of Licenciatura. It had as objectives: To identify auditory perceptions of the faulty ones in relation to the methods and resources used to teach health until then lived; To supply needs explained for the faulty ones auditory referring to contents of health through lectures and to Develop methods and resources that facilitate the process teaching-learning regarding contents of health among faulty auditory. The study was developed in 3 different phases: Diagnostical evaluation; Accomplishment of Lectures and Formative Evaluation. The population is constituted of students registered in the school, being the sample students part with superior age to 12 years. It was detected that the interviewees possessed prevention notions and transmission of diseases in general, but in relation to the diseases sexually transmissible, they ignored the transmission manners. It was also verified that they had little knowledge on sexuality and contraceptive methods. Comparing the diagnostical analisys data and of Formative analysis, it was observed that there were change of concepts and behaviors among the faulty ones. The teaching driven them requests the use of audiovisual resources in larger amount when compared to the normal studentsteaching. The development of continuous works is recommended with faulty using resources and appropriate plans and the investment in the teachers formation for the Special Education